Mechanics of Biological Systems and Materials, Volume 5 Proceedings of the 2012 Annual Conference on Experimental and Applied Mechanics - Prorok, Barton C.; Barthelat, François; Korach, Chad S.; Grande-Allen, K. Jane; Lipke, Elizabeth; Lykofatitits, George; Zavattieri, Pablo (Conference Proceedings of the Society for Experimental Mechanics Series, 2013)
Mechanics of Biological Systems and Materials, Volume 5: Proceedings of the 2012 Annual Conference on Experimental and Applied Mechanics, the fifth volume of seven from the Conference, brings together 31 contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Experimental and Applied Mechanics, including papers on:  Biological Materials & Mechanics Cell Mechanics Mechanics of Biomimetic Materials Mechanics of Brain Tissues and Structures Mechanics of Bone and Related Materials Multi-Scale Mechanics of Natural Fibers Indentation Methods in Soft Materials Imaging Methods in Biological Systems and Materials Mechanics of Tissue Damage Mechanics of Soft Materials and Tissues.